THE EFFECT OF COMPANY SIZE, AUDIT COMMITTEE AND LEVERAGE ON THE VALUE OF THE FIRM IN THE PROPERTY AND REAL ESTATE SECTOR IN INDONESIA - Kusnawan, Agus; Hakim, Mohamad Zulman; Sisca, Aranti; Suryanto, Febrian; Calista, Graciella Valencia; Mudittasari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The purpose of this research is to examine the influence of leverage, firm size, and audit committee on firm value. This study uses quantitative data where the population in this study uses the Property and Real Estate sectors listed on the Indonesia Stock Exchange for the period 2020 to 2021. This research used a Purposive Sampling Technique to obtain companies according to the criteria as a research sample. The data analysis method used is Panel Data Regression Analysis using the Eviews Version 12 application program. The results of this study found that leverage has an effect on firm value, company size has an effect on firm value, audit committee has an effect on firm value.